Discrimination Of Chinese Female Characters In The Latest Dimsum Novel By Clara Ng. - Khotimah, Nurul; Tleumuratov, Genjemurat; Tanasavate, Kuliga (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to describe the forms of discrimination, the causal factors, and the responses of Tionghoa ethnic women characters in facing discrimination in Clara Ng’s novel Dimsum Terakhir. Methodology: This research employed a descriptive qualitative method. The object of the study was Clara Ng’s novel Dimsum Terakhir. Data were collected through reading and note-taking techniques, and analyzed using feminist literary criticism. Data validity and reliability were ensured through semantic validation (expert judgment) and interrater-intrarater reliability procedures. Main Findings: Discrimination against Tionghoa women characters occurred in both domestic and public spheres. Domestic discrimination included seniority-based bias, while public discrimination involved racial slurs, denial of cultural rights, and physical violence. Political and ethnic factors were dominant causes. The characters primarily responded to discrimination with rejection, using verbal resistance and critical attitudes. Novelty/Originality of this study: This study highlights a specific intersection of gender and ethnic discrimination in Indonesian-Chinese women within literary narratives—an area still underrepresented. It advances feminist literary criticism by analyzing ethnic minority women’s voices in post-New Order Indonesia, enriching the understanding of layered discrimination in Southeast Asian literature.